Interleukin-35 suppresses pyroptosis and protects against neuronal death in retinal ischaemia/reperfusion injury. (July 2022) - Lin, Bingying; Li, Yangyang; Jiang, Nan; Huang, Siyu; Su, Wenru; Zhuo, Yehong
Abstract: Retinal ischaemia-reperfusion (I/R) is a pathological process in many eye disorders. Neuroinflammation and cell pyroptosis have been recognized as important in the pathogenesis of tissue damage in retinal I/R. Interleukin (IL)-35 is a novel heterodimeric cytokine that exhibits anti-inflammatory activity in various autoimmune diseases, but its role in retinal I/R and the underlying molecular mechanisms remain unexplored. This research investigated the effect of IL-35 on retinal I/R and the inhibition of pyroptosis and neuronal death. In our study, a murine retinal I/R model was used to explore the neuroprotective effect of recombinant IL-35 protein in vivo. Primary murine microglial cells in pyroptosis and retinal ganglion cells (RGCs) in oxygen and glucose deprivation/reoxygenation (OGD/R) models were employed to assess the antipyroptotic and antiapoptotic effects of IL-35 in vitro. The data showed that IL-35 decreases retinal damage, RGC death, and inner plexiform layer (IPL) thinning in mice with retinal I/R injury, with significant attenuation of pyroptosis in the retina. The study also demonstrated the anti-pyroptotic action of IL-35 in primary microglia stimulated with lipopolysaccharide (LPS) and adenosine triphosphate (ATP). Furthermore, primary RGC apoptosis induced by OGD/R was directly suppressed by IL-35, and IL-35-mediated neuroprotection was abrogated when miR-21 was blocked. In conclusion, our results suggest the mechanisms of RGC apoptosis and a new therapeutic target, IL-35, that exerts a robust neuroprotective effect against retinal I/R. Highlights: IL-35 decreases retinal damage, RGC death, and inner plexiform layer (IPL) thinning in mice with retinal I/R injury. IL-35 also attenuated the I/R-induced pyroptosis of mouse retina. IL-35 regulates LPS + ATP-induced pyroptosis in primary microglial cells in vitro. IL-35 protected against OGD/R-induced RGCs apoptosis in vitro. IL-35 treatment exerts neuroprotection against retina I/R injury through dual effect via miR-21-PDCD4 axis.